INSULIN TOLERANCE TEST VERSUS SHORT SYNACTHEN TEST TO ASSESS HYPOTHALAMUS-PITUITARY ADRENAL AIS IN PATIENTS POST-TRANSSPHENOIDAL SURGERY - S, Yi Koon; G, Kian Guan; S, Sharizal Bin Shudim; M, Hiryanti Binti Zakaria (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Patients undergoing pituitary surgery are routinely given perioperative glucocorticoids as protection for hypocortisolism. Early post-operative assessment should be done to determine hypocortisolism. However, there is still uncertainty regarding the most appropriate test to assess the integrity of hypothalamus-pituitary-adrenal (HPA) axis. The insulin tolerance test (ITT) is the gold standard, but this can be distressing and resourceintensive. Recently, many have been advocating the use of conventional short Synacthen test (SST) as an alternative to ITT. Our objectives were to evaluate the feasibility of SST and ITT to assess the HPA axis integrity post-surgery. METHODOLOGY This was a retrospective study of 5 patients who underwent pituitary surgery requiring ITT or SST for HPA assessment from March 2018 until March 2019. For the ITT, appropriate cortisol response was considered as a peak cortisol value of >500 nmol/L with adequate hypoglycaemia (plasma glucose <2.2 mmol/L). For the standard SST test, appropriate cortisol response was considered as a 60-minute value >550 nmol/L. RESULTS All 5 patients underwent transsphenoidal surgery for nonfunctioning pituitary adenoma. Of these, 2 had undergone ITT successfully, while the remaining 3 patients were unable to achieve significant hypoglycaemia. They proceeded to the SST to assess HPA axis integrity. CONCLUSION While the ITT is the gold standard to determine hypocortisolism, achievement of proper hypoglycaemia is proven difficult, with a 60% failure rate. SST provides a suitable substitute for patients who are unable to achieve adequate hypoglycaemia during ITT. It is an easier alternative and less labour-intensive compared to ITT. The preference of the patient is also important. However, the specificity of the short Synacthen test at a supraphysiological dose of 250 µg needs further evaluation, as such dose may overstimulate partially atrophied adrenals, leading to falsely reassuring results.